Screening and Determination of Potential Cellulolytic Bacteria from Mangrove Ecosystem - Ummi Mardhiah Batubara; Suparjo Suparjo; Hasna Ul Maritsa; Eko Pujianto; Meli Herlini (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
The mangrove ecosystem is a coastal wetland resource that has a diversity of biodiversities such as flora, fauna, and microorganisms. Microbes are an important component in the mangrove environment not only play a role in creating and maintaining boosters but also work as a source of biotechnology products. Cellulolytic bacteria are a group of cellulase-producing bacteria capable of breaking down cellulose into glucose monomers, and cellulose as a source of carbon and energy. This study aims to screen and determine the diversity of cellulolytic bacteria from the mangrove ecosystem. The research method was experimentally by exploring the diversity of cellulolytic bacteria from soil and sediment from the mangrove ecosystem. Three sampling locations were selected, such as litter soil, soil in the root area, and soil in the tidal area. Screening of potential bacteria producing cellulase enzymes was carried out by growing bacteria on Carboxy Methyl Cellulose (CMC) agar medium which was cultured for 48 hours at 37°C. The bacteria that produced the greatest cellulolytic activity were characterized by their morphological and physiological characteristics. The results of bacterial characterization were then adjusted according to Bergey's Manual of Determinative Bacteriology. Based on the analysis showed three bacterial isolates were obtained that had the largest cellulolytic activity index, namely MS06 (9.73), MS08 (5.41), and MS02 (5.07). The results showed that three isolates had the same characteristics as the bacterial genera Bacillus, Cellulomonas, and Micrococcus.